Revised Healthy Lifestyle‐Diet Index and associations with obesity and iron deficiency in schoolchildren: The Healthy Growth Study. (5th December 2013) - Manios, Y.; Moschonis, G.; Papandreou, C.; Politidou, E.; Naoumi, A.; Peppas, D.; Mavrogianni, C.; Lionis, C.; Chrousos, G. P.; ,
Abstract: Background: The Healthy Lifestyle‐Diet Index (HLD‐index), previously developed to assess the degree of adherence to dietary and lifestyle guidelines for primary schoolchildren, was revised according to updated recommendations. Τhe association of the revised HLD‐index (R‐HLD‐index) with obesity and iron deficiency (ID) was also examined. Methods: A representative sample of 2660 primary schoolchildren from Greece (9–13 years old) participating in the 'Healthy Growth Study' was examined. Twelve components related to dietary and lifestyle patterns were used to develop the R‐HLD‐index. Scores from 0 up to 4 were assigned to each one of these components, giving a total score ranging from 0 to 48. The associations between the R‐HLD‐index, obesity and ID were examined via logistic regression analysis. Results: The total score of the R‐HLD‐index calculated for each one of the study participants was found to range between 2 and 32 units, with higher scores being indicative of a healthier lifestyle and better diet quality. After adjusting for potential confounders, logistic regression analysis showed that an increase in the R‐HLD‐index score by one unit was associated with 6% lower odds for obesity. However, no significant association was observed between the R‐HLD‐index score and ID. Conclusions: The R‐HLD‐index may be a useful tool for public health policy makers and healthcare professionals when assessing diet quality and lifestyle patterns of primary schoolchildren. Identification of children with lower scores in the R‐HLD‐index and its individual components could guide tailored made interventions targeting specific children and behaviors.